Sociodemographic Study of HIV Positive Pregnant and HIV Positive Non Pregnant Women on ‘’ART’’ in a Tertiary Hospital in Port Harcourt, Nigeria - Odinga, Tamuno-Boma; Gabriel-Brisibe, Christine Umanu; Popnen, Tee Godwin Porobe; Azuonwu, Obioma; Opusunju, Boma H.; Ihua, Nnenna; Akuru, Udiomine Brantley; Akram, Muhammad (British Journal of Healthcare and Medical Research, 2022)
The influence of sociodemographic factors in the occurrence of HIV infection in Women is the focus of this paper. A hospital based cross-sectional study was conducted, involving HIV positive pregnant and non-pregnant women receiving care at the Rivers State University Teaching Hospital. The socio-demographic data was obtained using a structured questionnaire. Data were analyzed statistically on IBM SPSS Version25. The results revealed that women who were into various forms of business made up 37% of the subjects of study, while those who were employed were next at 25.8%. Women who were between 31 and 35 years of age formed the bulk of those who were HIV positive at 25.9% and those who were married were more commonly HIV positive at 70.9%. The findings of the study showed that married women that are inconsistently into various forms of businesses, not well educated, between 31-35 years were more infected with HIV